A comparative lipidomic study of the human placenta from women with or without gestational diabetes mellitus. (18th May 2022) - Jiang, Dongmei; He, Jin; Hua, Siyu; Zhang, Jiahua; Liu, Lan; Shan, Chunjian; Cui, Xianwei; Ji, Chenbo
Abstract : Lipidomics analysis was performed to characterize placental lipid composition of women with GDM. Significant differences in the type and content of lipids were observed and dysregulated lipid species showed strong association with glucose levels. Abstract : Gestational diabetes mellitus (GDM) is always accompanied by lipid disorders. The placenta serves as a center for lipid synthesis and transport and plays a critical role in establishing GDM. Thus, the changes in the type and content of lipids in the placenta may contribute to the development of GDM. Here, we performed an untargeted lipidomic analysis to profile the alterations of lipids in the placenta induced by GDM. Principal component analysis (PCA) was used to reduce the dimensionality of lipid data, and orthogonal projections to latent structures-discriminate analysis (OPLS-DA) was launched to show the differences in the lipid profile between the GDM group and normal controls. Additional multivariate data processing was carried out, including classification, pathway analysis and correlation analysis between dysregulated lipids and maternal blood glucose levels. We finally identified 1202 lipids in positive mode and 924 lipids in negative mode, of which 63 lipids were strongly associated with GDM. Notably, most dysregulated lipids were clustered in two major subtypes: glycerophospholipids and glycerolipids. Consistently, a significant down-regulation of glycerophospholipid metabolism was observed from pathway analysis. In addition, we found that SHexCer(d50:1), TAG(15:0/20:6/20:6) and PE(18:1e/21:2) were positively correlated with blood glucose levels, while PC(12:0/22:3), PC(22:4e/18:5) and PE(18:1e/26:4) showed negative correlations. Combining these lipids with fasting blood glucose showed high accuracy in the discrimination of women with GDM. In general, we explored the placental lipidomic abnormalities induced by GDM, and these findings may help us understand the pathological mechanisms of GDM.